Real-world pharmacovigilance of ofatumumab in multiple sclerosis: a comprehensive FAERS data analysis - Chen, Hui (Frontiers in Pharmacology, 2025)
BackgroundOfatumumab, a fully human monoclonal antibody targeting CD20, is approved for the treatment of relapsing multiple sclerosis. Comprehensive real-world safety data are crucial for informing clinical practice.MethodsThe FDA Adverse Event Reporting System database was utilized to perform a disproportionality analysis, covering reports from Q3 2020 to Q2 2024, in which ofatumumab was identified as the primary suspected drug. Statistical approaches used included the Reporting Odds Ratio, Proportional Reporting Ratio, Bayesian Confidence Propagation Neural Network, and Multi-item Gamma Poisson Shrinker. The timing of adverse events was assessed using the Weibull distribution model to highlight temporal risk patterns.ResultsKnown adverse reactions, such as injection site reactions and upper respiratory tract infections, displayed positive signals. Additionally, novel off-label adverse events, including brain fog, muscle spasms, and mood alterations, were identified, marking the first real-world evidence of these potential risks. Temporal analysis revealed that most adverse events occurred within the first month of treatment, indicating an early risk phase. Subgroup analysis demonstrated notable differences in adverse event profiles by gender and age, with males more prone to hyperhidrosis and older patients more susceptible to neurological symptoms.ConclusionThis real-world analysis of ofatumumab provides important safety insights, confirming known adverse reactions and identifying additional potential risks. Early and tailored monitoring protocols during the initial treatment phase, including regular neurological and psychiatric assessments, are recommended to optimize patient safety and outcomes. Prospective studies are recommended to validate these results and explore the underlying mechanisms.